Stimulating savings and mobilising investment flows to the small and medium enterprise sector : a case for venture capital - Wilson Drakes, Cheryll-Ann ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1997)
Explores the role of venture capital as a facilitator of sustainable economic development in the Caribbean.